2022
DOI: 10.1080/19490976.2022.2073131
|View full text |Cite
|
Sign up to set email alerts
|

A high-risk gut microbiota configuration associates with fatal hyperinflammatory immune and metabolic responses to SARS-CoV-2

Abstract: Protection against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and associated clinical sequelae requires well-coordinated metabolic and immune responses that limit viral spread and promote recovery of damaged systems. However, the role of the gut microbiota in regulating these responses has not been thoroughly investigated. In order to identify mechanisms underpinning microbiota interactions with host immune and metabolic systems that influence coronavirus disease 2019 (COVID-19) out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 62 publications
0
46
0
Order By: Relevance
“…This last study also suggested that the Bacteroidetes/Firmicutes ratio could be a predictor of mortality [7]. Intestinal dysbiosis has been shown to be associated with patient susceptibility to nosocomial infections, sepsis, organ failure and even COVID-19 disease severity [32][33][34][35][36][37].…”
Section: Critical Illnesses and The Gut Microbiotamentioning
confidence: 81%
“…This last study also suggested that the Bacteroidetes/Firmicutes ratio could be a predictor of mortality [7]. Intestinal dysbiosis has been shown to be associated with patient susceptibility to nosocomial infections, sepsis, organ failure and even COVID-19 disease severity [32][33][34][35][36][37].…”
Section: Critical Illnesses and The Gut Microbiotamentioning
confidence: 81%
“…Further, metabolite essentiality analysis identified butyrate, a microbiome-derived four-carbon short-chain fatty acid, as an essential metabolite in severe COVID-19, which plays an essential role in energy metabolism and intestinal homeostasis (Liu et al, 2018). Recently our integrative analysis of cytokines, metabolites, and microbiome features suggested a potential role of microbial-derived immunoregulatory processes in fatal outcomes in COVID-19 due to the failure of the negative feedback mechanism that should confine the cytokine storm (Albrich et al, 2022). Interestingly, MCTs are also involved in the butyrate transportation (Chang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that tryptophan metabolism was heavily disrupted in COVID‐19 patients during the acute phase of the infection, especially in those with the poorest outcomes. 4 Quinolinate is an excitotoxin that hinders neuronal function through multiple mechanisms including acting as an NMDA receptor agonist, and it indirectly drives accumulation of glutamate. In contrast, serotonin has essential modulatory effects on mood, anxiety, sleep, cognition, and memory.…”
Section: Figurementioning
confidence: 99%